Repeated Changes to the Gravitational Field Negatively Affect the Serum Concentration of Select Growth Factors and Cytokines - Stervbo, Ulrik; Roch, Toralf; Westhoff, Timm H.; Gayova, Ludmyla; Kurchenko, Andrii; Seibert, Felix S.; Babel, Nina (Frontiers in Physiology, 2019)
Space flights, some physical activities, and extreme sports can greatly alter the gravitational forces experienced by the body. Being a deviation from the constant pull of Earth, these alterations can be considered gravitational stress and have the potential to affect physiological processes. Physical cues play a vital role in the homeostasis and function of the immune system. The effect of recurrent alterations of the gravitational pull on the levels of soluble mediator such as cytokines is unknown. Parabolic flights provide a controlled environment and make these a suitable model to study the effects of gravitational stress. Utilizing this model, we evaluated the effects of short-term gravitational stress on serum concentration of cytokines and other soluble mediators. Blood was taken from 18 healthy volunteers immediately before the first parabola and immediately after the last. Samples taken on the ground at corresponding time points the day before were used to control for circadian effects. A wide range of soluble mediators was analyzed using a multiplex bead assay. We found that the rate-change of eight molecules was significantly affected by the parabolic flight. Among other functions, these molecules, EGF, PDGF-AA, PDGF-BB, HGF, IP-10, Eotaxin (CCL11), TARC, and Angiopoietin-2, can be associated with bone remodeling and immune activation. It is therefore possible that gravitational stress can have clinically relevant impact on the control of a wide range of physiological processes.